2017
DOI: 10.1080/24750573.2017.1380347
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childhood traumas, dissociation, and impulsivity in patients with borderline personality disorder comorbid with ADHD

Abstract: Objective: Previous studies reported that there were significant associations between Attention-deficit/hyperactivity disorder (ADHD) and borderline personality disorder (BPD). In this study, we aimed to examine complex relationship between childhood trauma, impulsivity, dissociative symptoms, and the impact of ADHD on this relationship in a sample of patients with BPD. Methods: Our samples consisted of 165 BPD patients (128 female, 37 male) and 165 healthy subjects (128 female, 37 male) of similar age and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
2
9
2
Order By: Relevance
“…Similarly, we did not evaluate childhood trauma, which can be considered as a common etiological factor for the subjects of interest. Consistent with this, a previous study suggested a strong association between impulsivity, childhood trauma, dissociation, and ADHD symptoms in patients with BPD [120]. Finally, the generalizability of the findings of the present study to the wider, nontreatment-seeking, mixed-sex population with SUDs requires further study.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, we did not evaluate childhood trauma, which can be considered as a common etiological factor for the subjects of interest. Consistent with this, a previous study suggested a strong association between impulsivity, childhood trauma, dissociation, and ADHD symptoms in patients with BPD [120]. Finally, the generalizability of the findings of the present study to the wider, nontreatment-seeking, mixed-sex population with SUDs requires further study.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that there were significant relationships between adult ADHD symptoms and impulsivity, childhood trauma, and dissociation. In addition, attentional and motor impulsiveness were found as the predictors of ADHD in BPD patients [23].…”
Section: Impulsivity and Its Relationship With Between Bpd And Adhdmentioning
confidence: 99%
“…The association between impulsivity and BPD is thoroughly documented (Kulacaoglu et al., 2017a, Kulacaoglu et al., 2017b). Paris (2005) reported that BPD expresses a wide range of impulsive behaviours including repeated suicide attempts, self-mutilation, substance abuse, sexual promiscuity, and reckless driving or eating behaviour.…”
Section: Introductionmentioning
confidence: 99%